Importance of NO3 radical in particulate nitrate formation in a southeast Chinese urban city: New constraints by δ15N-δ18O space of NO3-. (15th May 2021) - Zhang, Zhongyi; Cao, Lin; Liang, Yue; Guo, Wei; Guan, Hui; Zheng, Nengjian
Abstract: Stable nitrogen and oxygen isotopic signatures of nitrate in atmospheric fine-mode particulate (as δ 15 N–NO3 - and δ 18 O–NO3 - in PM2.5 ) was proposed to be useful in distinguishing the sources and oxidation chemistry of NO x (NO x = NO + NO2 ). In the present study, the chemical oxidation processes of atmospheric NO x in urban Nanchang, the capital of Jiangxi province, southeast of China were estimated based on the δ 15 N-δ 18 O space of NO3 - . Daily PM2.5 samples (n = 91) were collected during wintertime of 2017–2018 (1 November to 31 January), the major water-soluble inorganic ions and the dual isotopic signatures of NO3 - were measured. During the observations, the NO3 - concentrations in PM2.5 varied widely from 0.8 μg/m 3 to 57.7 μg/m 3, on average of 15.5 ± 6.7 μg/m 3 . The δ 15 N–NO3 - and δ 18 O–NO3 - also ranged widely, from −1.9‰ to +12.1‰ (+6.5 ± 3.7‰) and +69.1‰ to +95.5‰ (+85.9 ± 17.7‰), respectively. The daily δ 15 N–NO3 - was observed to be independent with the corresponding δ 18 O–NO3 - ( R 2 = 0.06, p > 0.05), which contrasted with many previous reports. By linking the δ 15 N–NO3 - to the NO x oxidation chemistry, we tried to explore the environmental significance of the δ 15 N-δ 18 O space of NO3 - . Our results suggested that the nocturnal pathways (e.g., N2 O5 hydrolysis and NO3 radical reacted with hydrocarbons: NO3 +HCs) dominated the chemical conversion of NO x to NO3 - in the wintertime of Nanchang, with an average fractional contribution of 60%. Interestingly, results also indicated the importance of the NO3 +HCs channel in NO x oxidation (on average of 33%), which can reach 45% during extreme nitrate aerosol polluted days. Our observations highlighted the importance of NO3 radical in NOx oxidation and particulate nitrate formation in polluted urban environment. Graphical abstract: Image 1 Highlights: The δ 15 N–NO3 - and δ 18 O–NO3 - ranged from −1.9‰ to +12.1‰ and +69.1‰ to +95.5‰, respectively. The daily δ 15 N–NO3 - was independent with the corresponding δ 18 O–NO3 - (R 2 = 0.06, p > 0.05). Results highlighted the importance of NO3 radical in NO x oxidation in polluted urban environment.